STRATEGI ADAPTASI MASYARAKAT PADA OBJEK WISATA MALALAYANG BEACH WALK STUDI KASUS DI PERUMAHAN MINANGA INDAH - Ricky Andesta Simanjorang (Universitas Sam Ratulangi, 2023)
The existence of social phenomena that appear in the midst of human life certainly has its own aspects, whether the presence of these social phenomena is able to adapt or adjust. Like the emergence of Malalayang Beach Walk which is one of the tourist attractions in Manado City, at the beginning of its presence caused pros and cons from the community. Not a few ripples from the public gave opinions regarding the construction of the Malalayang Beach Walk tourist attraction, which questioned the purpose of the attraction was built. Whether the community, especially the local community is able to adapt to the situation and conditions that arise, as well as the impact provided by the tourist attraction can be accepted and anticipated by the community. Various experiences and reasons for the people in Minanga Indah Housing in adapting or adjusting to the conditions that occur in Malalayang Beach Walk such as to take pictures, relax and unwind, gather with family or friends, exercise, or enjoy the culinary sold at the tourist attraction. In addition, people in Minanga Indah Housing are also accustomed and able to adjust to the congestion that occurs. Do not forget also that Malalayang Beach Walk has become an icon of Manado City, and has become one of the good tourist attractions to visit. Keywords: Adaptation Strategy, Tourist Attractions, Malalayang Beach Walk